Management of Reintroduced Lions in Small, Fenced Reserves in South Africa: An Assessment and Guidelines - Miller, S.M.; Bissett, C.; Burger, A.; Courtenay, B.; Dickerson, T.; Druce, D.J.; Ferreira, S.; Funston, P.J.; Hofmeyr, D.; Kilian, P.J.; Matthews, W.; Naylor, S.; et al. (South African journal of wildlife research, 2013)
Managers of African lions (Panthera leo) on reserves where they have been reintroduced increasingly face challenges associated with ecological regulation,genetic degradation and increased susceptibility to catastrophic events. The Lion Management Forum (LiMF) was formed in 2010 to define these challenges and explore possible solutions with the view to developing appropriate management guidelines. LiMF bases its recommendations on the ecologically sound premise that managers should, as far as possible, mimic natural processes that have broken down in reserves, using proactive rather than reactive methods, i.e. management should focus on causal mechanisms as opposed to reacting to symptoms. Specifically, efforts should be made to reduce population growth and thus reduce the number of excess lions in the system; disease threats should be reduced through testing and vaccination whenever animals are translocated; and genetic integrity should be monitored. The latter is particularly important, as most of these reserves are relatively small (typically <1000 km2). An adaptive management framework is needed to implement the guidelines developed here on reserves across the country, with regional nodes addressing more local genetic issues, within an overall national plan. Ongoing monitoring and scientific assessment of behavioural, population and systemic responses of lion populations and responsive modification of the guidelines, should improve management of lions on small reserves in South Africa. This approach will provide a template for evidence-based conservation management of other threatened species. Ultimately ‘National Norms and Standards’ must be established and a ‘National Action Plan’ for lions in South Africa developed.